Análise das variáveis contingenciais nas adaptações das práticas de produção enxuta na implementação de sistemas de produção específicos (XPS) - Medeiros , Nayara Cardoso de (2016)
Facing the need for adaptations of lean production to the characteristics of each organization, researchers have questioned the universality of this production system. These adjustments may be related to the contextual characteristics of the manufacturing system of each organization and can lead to the development of company-specific production systems, or simply XPSs. Thus, the aim of this research is to analyze how the contingency variables of a manufacturing system influence the adaptations of lean production practices for the implementation of an XPS. The research was developed through case studies conducted in two manufacturing plants, one of the electronics industry and other from the home appliances sector, both located in the city of Manaus/AM. The data were collected mainly through semi-structured interviews and on-site observation. Through this research, adaptations have been identified, not in the lean practices but in the manufacturing system of the companies, i.e., instead of the contingency variables demand adaptations to the formation of a company-specific production system, the Toyota system (universal approach) remains as the main driver of change in their own manufacturing system variables. Based on this observation, two potential outcomes can be inferred: either the influences of contingency variables may be irrelevant or they are not perceived by managers. Finally, in neither of the cases studied was identified the creation of specific practices tailored to the company. On the contrary, it was found the use of the same traditional practices of TPS. On the other hand, it was clearly observed the intention of creating an identity for the XPS, much more as a motivational factor than as a true adaptation. This evidence allowed the development of three propositions that deserve further research.